VALIDATION OF A BIOANALYTICAL REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC METHOD FOR THE QUANTITATION OF NYSTATIN IN AN ANIMAL MODEL AFTER INTRANASAL IN SITU GEL ADMINISTRATION - MARZUKA, KAZI; MOHAMED HASSAN, DEHGHAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of the study was to develop and validate a bioanalytical reverse-phase high-performance liquid chromatographic (HPLC) method for the estimation of nystatin in rat plasma after intranasal administration. Methods: The reversed-phase HPLC system was equipped with a Luna C18 column, the mobile system comprised of methanol, water, and dimethylformamide (55:30:15) and the flow rate was set at 0.9 ml/min. Results: The elution time for nystatin was 4.096±0.025 min. The calibration curves constructed in rat plasma were linear from 0.25 to 50 μg/ml. The lower limit of quantification (LOQ) was found to be 0.25 μg/ml. The standards for accuracy and precision of the intra- and inter-day variation studies were in the acceptable ranges as per the FDA guidelines. Conclusion: The LOQ value determined by the proposed method was noted to be satisfactory for inspecting the plasma pharmacokinetics of nystatin in rats’ post-administration of a nasal in situ gelling liquid crystalline precursor formulation in an in vivo study.